N-Acetylcysteine for the Management of Non-Acetaminophen Drug-Induced Liver Injury in Adults: A Systematic Review - Sanabria-Cabrera, Judith; Tabbai, Sara; Niu, Hao; Alvarez-Alvarez, Ismael; Licata, Anna; Björnsson, Einar; Andrade, Raul J.; Lucena, M. Isabel (Frontiers in Pharmacology, 2022)
Introduction: Idiosyncratic Drug-induced liver injury (DILI) is a rare adverse reaction to drugs and other xenobiotics. DILI has different grades of severity and may lead to acute liver failure (ALF) for which there is no effective therapy. N-acetylcysteine (NAC) has been occasionally tested for treatment of non-acetaminophen drug-induced ALF (NAI-ALF). However, limited evidence for its efficacy and safety is currently available. Our aim is to elucidate the benefit and safety of NAC in DILI and evaluate its hepatoprotective effect. Methods: We conducted a systematic review to evaluate the management and prevention focused on NAC in idiosyncratic DILI. Main outcomes included mortality due to DILI, time to normalization of liver biochemistry, transplant-free survival, and adverse events. We included clinical trials and observational studies, either prospective or retrospective. Results: Eleven studies were included after literature screening. All studies had different methodologies and some of them with important risk of bias that may lead to interpret their findings with caution. Majority of the studies proved NAC efficacy in a cohort of patients with ALF due to different etiologies and where DILI represented a subgroup. NAC seemed to improve transplant-free survival however its benefit was inconclusive in term of overall survival. With regard to safety, NAC showed an adequate safety profile. In prevention studies, NAC showed a possible hepatoprotective effect however this finding is limited for the lack of studies and presence of bias. Conclusions: NAC treatment seems to have some benefit in non-acetaminophen drug-induced liver failure patients with acceptable safety, however due to the lack of evidence and limitations detected across studies, its benefit must be corroborated in clinical trials with adequate methodology.